Partisipasi Masyarakat Dalam Pengembangan Desa Wisata Jatirejo Kota Semarang - Damayanti, Yola Mutia; Mulyono , Sungkowo Edy (Universitas Pahlawan Tuanku Tambusai, 2024)
Jatirejo Tourism Village is one of the pilot tourism villages in Semarang City that has its own attraction for tourists. The implementation of good quality tourism village development certainly requires community participation. The purpose of this research is to find out and describe community participation and to find out the supporting and inhibiting indicators during the development of Jatirejo Tourism Village. This research used a descriptive qualitative approach involving the Head of Village, Head of Deswita Management, Pokdawis Management, and the Jatirejo Village community. Data collection was conducted through observation, interviews, and documentation. The data obtained will later be analyzed through source triangulation. The results prove that the review of community participation in the development of Jatirejo Tourism Village based on the sequence of implementation and benefit taking has not taken place effectively and evenly. The decision-making and evaluation processes have not been optimized because the management of Deswita and Pokdarwis did not involve the community. Factors driving community participation in the development of Jatirejo Tourism Village include willingness, opportunity and ability. Meanwhile, the inhibiting factors are individual nature, demographics, and economic conditions. It is expected that Jatirejo Village can make efforts to increase the willingness and interest of the community in participating and contributing to the development of Jatirejo tourist village, through the utilization of its local potential to improve the welfare of the community.